Congenital unilateral facial nerve paralysis in a Warmblood filly. (24th June 2017) - Schön, S.; Wehrli Eser, M.; Kircher, P. R.; Sydler, T.; Augsburger, H.; Ohlerth, S.; Beckmann, K.; Fürst, A. E.
Summary: A 17‐month‐old Warmblood filly was referred to our clinic for evaluation of congenital facial nerve (FN) paralysis. Clinical examination revealed a right‐sided facial paralysis with mild masticatory muscle atrophy, mild dysphagia and exposure keratitis. Apart from the FN deficits, neurological examination of the remaining cranial nerves showed no abnormalities. Magnetic resonance imaging (MRI) examination using a 3.0 Tesla scanner showed that in comparison to the left FN, the intracranial section of the right FN between the pons and internal acoustic canal was thinner, whereas it appeared indistinct and thickened within the internal acoustic canal and facial canal. Signs of meningitis or encephalitis were not present on MRI. Cerebrospinal fluid analysis showed mild pleocytosis. The owner of the filly requested euthanasia due to the guarded prognosis. At necropsy, the intracranial section of the right FN was macroscopically thinner than the left side and within the facial canal, a 5 mm tissue stump could be identified with an absent extracranial part of the right FN. Histological examination of the brain stem showed different architecture of the left and right motor nuclei of the FN: in the left nucleus, motor neurons of a normal size and well stainable Nissl bodies were present, whereas in the right nucleus, neurons with Nissl bodies were decreased in number and size. Further, a cytoplasmic rich cell population with a nucleus size compatible with normal neurons was present. These cells were suspected to be atrophic neurons. The tissue stump within the facial canal was histologically identified as connective tissue. Unilateral malformation of the FN has not previously been described in the horse. This filly showed a right‐sided, intracranial hypoplasia accompanied by an extracranial aplasia of the FN causing complete, congenital facial nerve paralysis, which corresponded to a difference in the architecture of the affected motor nucleus of the FN.